A Compact Inverted Y Slot Rectangular Microstrip Patch Antenna for Bluetooth Applications - Ramesh Kumar Verma; D K Srivastava (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper a compact and slotted rectangular microstrip antenna is designed at 3.00GHz frequency and it is loaded by inverted Y slot so that the bandwidth of microstrip antenna is improved upto 36.30%. The area of radiating patch for 3.00GHz frequency is 711.36mm2.The proposed antenna design has frequency band in the frequency range 2.097GHz to 3.030GHz. The proposed antenna is resonating at 2.45GHz and area of radiating patch at this frequency is 1077.97mm2. Hence the size of antenna is reduced by 34% corresponding to resonance frequency 2.45GHz. This frequency band is suitable for Bluetooth and other wireless communication applications. The proposed slotted microstrip antenna is directly feed by 50Ω microstrip line feed. The proposed antenna is simulated by IE3D simulation software based on method of moments.